2019
DOI: 10.20343/teachlearninqu.7.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Undergraduates' Reports of Co-curricular Involvement Across the Degree

Abstract: The study discussed in this article investigated university student beliefs and behaviours with respect to co-curricular activities among incoming (n=983), mid-degree (n=173), and graduating (n=1006) students. When asked about their most significant learning experiences during their time at university, graduating students were more likely to report on co-curricular activities than those related to coursework. However, participation in co-curricular activities was not related to graduating students' feelings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Borwein (2014) suggested that community-based volunteer experiences may be seen as important for entry-level positions at a time when less than 25% of employers are willing to consider job applicants with no related experience. External career-related opportunities, such as field education experiences and co-curricular activities, enhance career preparedness in social work fields (Beddoe et al, 2018;Martini et al, 2019). Students with hands-on experience are better equipped to identify their desired future roles, positively affecting their motivation, willingness, and performance (Inceoglu et al, 2019).…”
Section: Career Clarity and Volunteer Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Borwein (2014) suggested that community-based volunteer experiences may be seen as important for entry-level positions at a time when less than 25% of employers are willing to consider job applicants with no related experience. External career-related opportunities, such as field education experiences and co-curricular activities, enhance career preparedness in social work fields (Beddoe et al, 2018;Martini et al, 2019). Students with hands-on experience are better equipped to identify their desired future roles, positively affecting their motivation, willingness, and performance (Inceoglu et al, 2019).…”
Section: Career Clarity and Volunteer Experiencesmentioning
confidence: 99%
“…These outcomes can be found through service-learning, co-curricular, or volunteer experiences identified as high-impact practices by the Association 2007). High-impact practices are defined as those experiences that help undergraduates develop realworld skills through hands-on applied learning (Martini et al, 2019). To date, however, there are few studies that explore the correlation between these high-impact practices and feelings of career clarity and preparedness (Martini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Students do not automatically recognize how experiences and assignments are related to the development of the skills needed for professional success (Halonen & Dunn, 2018; Martini et al, 2015), and many students do not have the language needed to articulate the skills they do have (Martini et al, 2019). Thus, in addition to assessing interests and work values, students should regularly assess the development of knowledge and skills included in Guidelines 2.0 and valued by employers.…”
Section: A Comprehensive Psychology Workforce Literacy Modelmentioning
confidence: 99%
“…There is a growing body of literature examining students' involvement in co-curricular activities [4,16]. Elias [17] has defined co-curriculars as comprising "university-affiliated activities that are outside the academic curricula and provide opportunities for intentional learning and development" (p. viii).…”
Section: Literature Review Co-curriculars Involvementmentioning
confidence: 99%
“…[1,3,18]. As suggested by previous researchers, co-curricular involvement has been linked to a range of positive student outcomes, including: career-related professional skills acquisition and competencies developed, such as communication, leadership, and teamwork [3,5,16], academic achievement and persistence [19], ethical development [18], and cognitive development [20,21]. Students, for example, are aware of the importance of co-curricular experiences in their future employment [22].…”
Section: Literature Review Co-curriculars Involvementmentioning
confidence: 99%